Taklik Talak dan Akibat Hukumnya dalam Kompilasi Hukum Islam Perspektif Teori Feminis - Nur Azizah Hutagalung; Edi Gunawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2019)
Taklik talak is the promise of the husband who was handed over to four conditions, namely leaving his wife for two consecutive years, not giving a mandatory salary for three months, hurting his wife's body, and not caring about his wife for six months. If the four conditions are realized, then there will be a violation of taklik talak. The taklik talak breach gave birth due to the khuluk law which had implications for the release of wife's rights to the iddah and mut'ah livelihood, and the wife was obliged to pay the ransom of the divorce. Based on the khuluk background, namely the violation of taklik talak indicated by domestic violence, and the legal consequences that accompany it, the law is discriminatory and places women in a low position. Such a situation is a form of gender inequality. Feminist schools strongly oppose gender inequality in law, especially Legal Theory Feminists. Feminist Legal Theory is a gender stream that focuses on legal criticism of gender bias.